1990
DOI: 10.1093/carcin/11.6.1013
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative DNA and RNA damage in rat liver due to acetoxime: similarity to effects of 2-nitropropane

Abstract: Acetoxime (ACO) and 2-nitropropane (2-NP), both industrially important chemicals and known hepatocarcinogens in rats, induced increased levels of 8-hydroxy-guanine in liver DNA and RNA of male Sprague-Dawley and F344 rats after either oral or i.p. administration. Both compounds also produced qualitatively the same patterns of other apparent modifications of liver DNA and RNA nucleosides, discernible by HPLC with electrochemical detection. Six hours after administration, the effects of 2-NP on liver nucleic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
4

Year Published

1991
1991
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 0 publications
1
17
1
4
Order By: Relevance
“…The development of the nucleic acid modifications DX1 and 8-aminoguanosine and the increased formation of 8-oxoguanine in DNA and RNA were detected also after administration of the ketoximes acetone oxime (Guo et al 1990;), 3-pentanone oxime, 4-heptanone oxime (Hussain et al 1991), cyclopentanone oxime (Conaway et al 1991) and cyclohexanone oxime (Hussain et al 1991) and of the secondary nitroalkanes 2-nitropropane, 2-nitrobutane, 3-nitropentane, 2-nitroheptane, 2-nitrooctane and nitrocyclopentane (Conaway et al 1991). The ketoximes were less effective than their oxidation products, the corresponding secondary nitroalkanes (Guo et al 1990;Hussain et al 1990). The DNA-modifying effects of both substance groups were stronger in male animals than in females (Guo et al 1990).…”
Section: In Vivomentioning
confidence: 98%
See 2 more Smart Citations
“…The development of the nucleic acid modifications DX1 and 8-aminoguanosine and the increased formation of 8-oxoguanine in DNA and RNA were detected also after administration of the ketoximes acetone oxime (Guo et al 1990;), 3-pentanone oxime, 4-heptanone oxime (Hussain et al 1991), cyclopentanone oxime (Conaway et al 1991) and cyclohexanone oxime (Hussain et al 1991) and of the secondary nitroalkanes 2-nitropropane, 2-nitrobutane, 3-nitropentane, 2-nitroheptane, 2-nitrooctane and nitrocyclopentane (Conaway et al 1991). The ketoximes were less effective than their oxidation products, the corresponding secondary nitroalkanes (Guo et al 1990;Hussain et al 1990). The DNA-modifying effects of both substance groups were stronger in male animals than in females (Guo et al 1990).…”
Section: In Vivomentioning
confidence: 98%
“…It has been suggested that also the DNA-damaging effects of the ketoximes result from in vivo oxidation to the corresponding secondary nitroalkanes (Fiala et al 1995;Hussain et al 1990); Mirvish et al 1982, which are metabolized in the liver in asulfotransferase-dependent reaction to form areactive, DNA-binding species.…”
Section: M Echanism Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other reports have demonstrated that F-344 rats are more prone than S-D rats to develop inflammatory granulomas when exposed to various chemicals and pharmaceutical agents [Ward et al, 1993;Schwab, 1977a, 1977b]. F-344 rats are more susceptible than S-D rats to oxidative stress in the liver, as measured by necrosis and DNA adduct formation, when exposed to diquat [Smith et al, 1985] and 2-nitropropane [Hussain et al, 1990].…”
Section: Introductionmentioning
confidence: 98%
“…It has been reported that high doses of methyl ethyl ketoxime may induce hematopoietic and central nervous system dysfunctions and result in developmental abnormalities (Schulze & Derelanko, 1993; Burka et al ., 1998; Derelanko et al ., 2003). Some ketoximes have also been suggested to act as hepatocarcinogens in rats because their oral and intraperitoneal administrations have been reported to increase 8‐hydroxyguanine levels in the liver DNAs and RNAs of male Sprague Dawley and F344 rats (Hussain et al ., 1990). …”
Section: Introductionmentioning
confidence: 99%